2022
DOI: 10.1038/s41388-022-02450-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MYC interaction network in B-cell lymphoma via histone deacetylase 6 inhibition

Abstract: Overexpression of MYC is a genuine cancer driver in lymphomas and related to poor prognosis. However, therapeutic targeting of the transcription factor MYC remains challenging. Here, we show that inhibition of the histone deacetylase 6 (HDAC6) using the HDAC6 inhibitor Marbostat-100 (M-100) reduces oncogenic MYC levels and prevents lymphomagenesis in a mouse model of MYC-induced aggressive B-cell lymphoma. M-100 specifically alters protein-protein interactions by switching the acetylation state of HDAC6 substr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…The HDAC6 inhibitor ricolinostat has been found to induce an unfolded protein response and overload the proteasome in DLBCL cells [ 188 ]. Moreover, the HDAC6 inhibitor treatment of DLBCL and B-cell lymphoma cells in Eµ-Myc mice induced MYC degradation, apoptosis, and inhibition of lymphomagenesis [ 189 ].…”
Section: Therapeutic Targeting Of Histone Modificationsmentioning
confidence: 99%
“…The HDAC6 inhibitor ricolinostat has been found to induce an unfolded protein response and overload the proteasome in DLBCL cells [ 188 ]. Moreover, the HDAC6 inhibitor treatment of DLBCL and B-cell lymphoma cells in Eµ-Myc mice induced MYC degradation, apoptosis, and inhibition of lymphomagenesis [ 189 ].…”
Section: Therapeutic Targeting Of Histone Modificationsmentioning
confidence: 99%
“…Interestingly, in the Chalcone case, both effects led to anticancer activity. Posttranslational modifications of Hsp40 (farnesylation) and its binding partners (acetylated tubulin) were also described as targetable Hsp40-modulatory mechanisms [ 125 , 131 , 132 , 133 ]. In this way, potential combination partners such as farnesyltransferase inhibitors and HDAC6 inhibitors emerged as modulators of the Hsp70-Hsp40 axis, which might be considered for future in vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Selective inhibition of cytoplasmic HDAC6 by the HDAC6 inhibitor 34 ( Figure 5 , marbostat) led to MYC degradation and apoptosis in MYC-overexpressing B-cell lymphoma cells. It was shown that HDAC6 inhibition by compound 34 led to hyperacetylation of tubulin followed by enhanced binding of DNAJA3 to hyperacetylated tubulin in the cytoplasm of B-cell lymphoma cells, which led to enhanced Myc degradation [ 133 ].…”
Section: Modulators Of Co-chaperone Hsp40mentioning
confidence: 99%
“…To generate experimentally used WT and KO mice, RD and RDF mice were bred to be heterozygous for Rad18. To obtain Rad18;delCre; Eµ–Myc (RDM) and Rad18;DelCre;FlpE;Emμ-myc (RDFM) mouse lines, RD and RDF mouse lines were crossed with heterozygous mice regarding Eµ–Myc on a C57BL/6 background 39 , originally provided from Jackson Laboratory. Mice developing tumours were immediately sacrificed via cervical dislocation after reaching humane end point criteria.…”
Section: Methodsmentioning
confidence: 99%